The Association between Age-Related Macular Degeneration and the Risk of Mortality - Wang, Peipei (Biomed Res Int, 2017)
Studies have investigated the association between age-related macular degeneration (AMD) and subsequent risks of mortality, but results have been equivocal. We conducted a comprehensive analysis of prospective cohort studies to assess the association of AMD and the risk of mortality in the general population. We searched PubMed and EMBASE for trials published from 1980 to 2016. We included 11 cohort studies that reported relative risks with 95% confidence intervals for the association of AMD and mortality, involving 57,069 participants. In a random-effects model, the adjusted RR (95% confidence interval) associated with AMD was 1.09 (1.02–1.17) for all-cause mortality. Findings from this research provide support that persons with AMD had a higher subsequent risk of mortality than persons without AMD.